2009
DOI: 10.5014/ajot.63.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Pet Ownership as a Meaningful Community Occupation for People With Serious Mental Illness

Abstract: The key finding supports the hypothesis that pet owners with serious mental illness living in the community demonstrate higher social community integration. Implications for future research and practice are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 72 publications
3
68
0
Order By: Relevance
“…In a sample of persons with persistent mental illness, the EMAS demonstrated adequate test-retest reliability and a low positive relationship with life satisfaction (Goldberg et al). Scores for the EMAS have also been shown to vary as a function of pet ownership for persons with serious mental illnesses (Zimolag & Krupa, 2009). In a study involving older adults (Eakman, Carlson, & Clark, in press) convergent validity was evidenced by significant correlations between the EMAS and measures of meaning and purpose in life, depressive symptomology, life satisfaction, and health-related quality of life.…”
mentioning
confidence: 99%
“…In a sample of persons with persistent mental illness, the EMAS demonstrated adequate test-retest reliability and a low positive relationship with life satisfaction (Goldberg et al). Scores for the EMAS have also been shown to vary as a function of pet ownership for persons with serious mental illnesses (Zimolag & Krupa, 2009). In a study involving older adults (Eakman, Carlson, & Clark, in press) convergent validity was evidenced by significant correlations between the EMAS and measures of meaning and purpose in life, depressive symptomology, life satisfaction, and health-related quality of life.…”
mentioning
confidence: 99%
“…Considered through this lens, pet ownership has potential as a form of occupation which can improve the quality of living and life satisfaction levels of people with serious mental illnesses as well (Goldberg et al 2002;Zimolag and Krupa 2009). Positive effects from companion animal studies are backed up by reports of people with serious mental illnesses reporting that they felt the animals provided opportunities to care for a living creature, without the complexities often present in a human relationship (De Souza 2000).…”
Section: Wysong 2000mentioning
confidence: 99%
“…Contact with pets, caring for and ownership of pets, provides abundant occupational opportunities with personal and social meaning, involving many activities and experiences which enrich and enhance human lives (Zimolag and Krupa 2009). Most pet owners have reported that pets provided them with added opportunities for relationships, fun, play, exercise and a sense of security (Willis 1997).…”
Section: Wysong 2000mentioning
confidence: 99%
See 2 more Smart Citations